Rétroaction corrective synchrone et écriture collaborative en ligne : perceptions d’enseignants de français langue seconde - Papin, Kevin; Michaud, Gabriel (Canadian Journal of Applied Linguistics, 2023)
With the recent surge in remote teaching, collaborative writing (CW) tasks, which have been shown to help the development of second language (L2) writing skills (Elabdali, 2021), are increasingly taking place online. Such format allows the L2 teacher to provide synchronous written corrective feedback (SWCF) to learners, who can then collaboratively address errors in real time. However, few studies have focused on teachers’ perceptions in the context of an online L2 French course. This case study therefore explores L2 French teachers’ (N = 3) perceptions regarding the implementation, in their advanced written French course, of two online CW tasks (Google Docs), during which they provided SWCF to their students (N = 46), who collaborated in small groups via videoconferencing (Zoom). After the two tasks, teachers shared their views on the affordances and limitations of such pedagogical practice in a semi-structured focus group interview conducted online (Zoom). Content analysis of the interview transcriptions indicates that while teachers had overall positive perceptions of this practice and saw its potential for L2 French teaching and learning, some concerns regarding practicality and implementation of SWCF during online CW emerged. Best practices regarding the provision of SWCF during such CW tasks are discussed.